(untitled) (INTEGRATION PROCEEDING, 2023)
Indonesia has natural wealth that is useful for researching all contents that have the potential to become herbalmedicines that can be made into practical preparations as therapeutic agents for gastric ulcers, one of which is papaya plants which are useful for the treatment of protecting the gastric mucosa. Papaya leaf extract with a dose of 100 mg can prevent ulcers the same as conventional medicine. Controlled-release preparations aim of prolonging the residence time of the drug in the gastrointestinal tract and regulating the rate and amount of drug released. Papaya leaf extract mucoadhesive tablets were formulated using a variation of mucoadhesive polymer, namely Carbopol with Na. CMC is expected to increase the strength and duration of contact between the drug-containing polymer and the mucosal surface. The purpose of this research is to determine the most optimal formulation and the effect of the combination of Carbopol and Na matrices CMC on mucoadhesive tablet formulation of papaya leaf extract. The method used is a quasiexperimental design by comparing the results of the intervention with a control group from the evaluation of the formulation and based on the analysis of the simplex lattice design. Results: The results of the evaluation of the LOD test powder, the flow properties of all formulations met the requirements and the angle of repose in the formulation I, compressibility at FI and FIII met the requirements. The resulting tablets have a color, odor and shape. Weight uniformity, friability, in vitro were in accordance with the requirements and in the evaluation of hardness none of the formulations met the requirements. The most optimal formulation is formulation I based on simplex lattice design analysis with a combination concentration of Carbopol 30 mg and Na. CMC 40 mg and there is an effect of the combination of Carbopol matrix and Na. CMC is on the formulation of mucoadhesive tablets.